The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1142/s1793292006000288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reaction Temperature on the Production of Carbon Nanotubes

Abstract: A floating catalyst chemical vapor deposition (FC-CVD) method was designed and fabricated to produce high quality and quantity carbon nanotubes. The reaction temperature was optimized to produce high yield and purity of the carbon nanotubes. The reaction temperatures were varied from 500–850°C. The result shows that carbon nanotubes were observed from 600°C to 850°C with maximum numbers and high purity at 850°C. The diameter range of CNTs varied from 2 to 55 nm. The results of the present investigation suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The experimental set-up used to synthesize the Multiwall Carbon Nanotubes is similar to that reported by Muataz et al [28, 29]. The Floating Catalyst Chemical Vapor Deposition (FC-CVD) reactor has been used to produce CNTs.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental set-up used to synthesize the Multiwall Carbon Nanotubes is similar to that reported by Muataz et al [28, 29]. The Floating Catalyst Chemical Vapor Deposition (FC-CVD) reactor has been used to produce CNTs.…”
Section: Methodsmentioning
confidence: 99%
“…The temperature influence on the structure of the carbon materials has been emphasized. It is generally accepted that carbon materials are formed by carbon atom dissolving, diffusing, and precipitating through the catalyst droplets in CVD process [37,38]. Figure 10 shows the polarization curves of PEM fuel cells fabricated using the CNx nanotubes grown at 800 and 900°C as cathode catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Muataz et al [68] studied the role of reaction temperature in CNTs synthesis by floating catalyst method, in which benzene and ferrocene were utilized as carbon precursor and catalyst, respectively. They pointed out that MWCNTs synthesis occurs at temperatures greater than 500 • C and maximum wall numbers with less impurity is obtained at 850 • C (see Fig.…”
Section: Temperaturementioning
confidence: 99%
“…Although in a few rare cases, CNTs were produced at temperatures higher than 1000 • C [67,72], but most reported that the CVD products are in non-tubular form of carbon at these temperatures [12,47,48,68]. It can be attributed to the fact that not only pyrolysis of carbon sources is generally promoted around 1000 • C, but also pyrolysis of the CNTs will begin.…”
Section: Temperaturementioning
confidence: 99%